The Rise of Post-Confucion Knowledge Economies - Marginson, Simon (International Higher Education, 2012)
In East Asia and Singapore tertiary participation and scientific output are rising very rapidly, underpinned by economic growth, Confucian education values at home and the focused policies of governments determined to catch-up to North American and Western Europe. The leading research universities in China, Hong Kong SAR, South Korea, Taiwan and Singapore are on course to join Japan in the front rank of the world's higher education institutions.